HUBUNGAN KEPEMIMPINAN DAN KOMUNIKASI DALAM PENUGASAN TIM DENGAN KELENGKAPAN DOKUMENTASI ASUHAN KEPERAWATAN - Amalia (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
The vision, mission and objectives of a hospital from a nursing room greatly influence theestablishment of a nursing care assignment method, the availability of nursing staff both innumber and qualifications, the level of dependence and mobility of the client and the availabilityof nursing procedures and standards. The purpose of this study was to identify leadership andcommunication relationships in team assignments with complete nursing care documentation atthe hospital. Using the quantitative method of Cross Sectional design, the research subjects werenurses in the inpatient ward of the Palembang Mother Hospital with a sample of 81 nursesdetermined using purposive sampling. Data sources were obtained by using questionnaires andinterviews, which were conducted on November 24 - December 11 2018. Analysis of data usingthe chi-square test. The results of leadership research in carrying out team assignment methodswere lacking (76.5%) and communication was also lacking (74.1%) while the evaluation ofnursing care documentation for completeness was complete (69.1%). For the p-value of theleadership variable (0,836) and communication has p-value (0,749), it is concluded that there isno relationship between leadership and communication in the assignment of the team withcomplete documentation of nursing care in the inpatient ward of the Bunda Palembang Hospital.Based on the results of the study, it is expected that the management of the hospital will improveits managerial function in improving the quality of nursing services, especially in communicationand leadership in evaluating nursing care documentation.